Penerapan Model Pembelajaran Teams Games Tournaments (TGT) Dalam Meningkatkan Keaktifan Belajar Siswa Pada Pembelajaran Tematik - Rina Rahmi; Husnul Farida (Jurnal Transformasi Pendidikan Dasar, 2025)
This study examines the application of the Teams Games Tournaments (TGT) learning model to increase the learning activeness of third-grade students of MIN 10 Aceh Barat in thematic learning. This type of research uses classroom action research (PTK) with data collection techniques that include observation, tests, and documentation. Furthermore, it was analyzed using the percentage formula. The results showed that the use of the TGT model in thematic learning showed that teacher activity in cycle I reached 63.46% and increased in cycle II by 92.30%. Student activity in cycle I reached 59.61% and increased in cycle II by 88.46%. Student learning activeness on the theme “Loving animals and plants” is very high, it is known based on students' answers to the questions in the questionnaire where in cycle I obtained a percentage of 62.50% and increased in cycle II to 93.75%. Thus, it can be concluded that the application of the TGT model can increase student learning activeness.